Studi Literature Review: Analisis Kualitatif Penggunaan Diksi Dalam Media Sosial Facebook - Juan Syakir Haziq; Usiono Usiono (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
The use of diction on social media, especially on Facebook, plays a very important role in shaping perceptions, influencing opinions, and building personal or collective identities. This article aims to analyze the use of diction in Facebook posts using a qualitative approach. This research uses the discourse analysis method to understand how word choice affects communication in the digital space. In this study, data was collected through a survey. The case of state exemption was purposively selected. The results of the analysis show that the use of diction on Facebook is strongly influenced by individual communication goals, socio-cultural context, and group dynamics involved in digital interactions. The diction used can reflect the values, attitudes, and moods of its users.